IMPLIKASI NILAI SINISME DALAM MENGUPAYAKAN NILAI MORAL PADA KEMAJUAN GLOBALISASI PERSPEKTIF AL-QUR’AN - Dodi Adrian Febriansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of globalization actually has a positive and negative impact on moral education. Overcoming the progress of globalization requires limitations so that it is not excessive in following the progress of globalization, especially technology. Therefore, Cynicism is a school of Greek philosophy aimed at obtaining true happiness by rejecting all conventional values. This often happens due to the premise that the morality of today's decline is due to conventional values and also the influence of technological advances and globalization. This caused a significant decline in morale. The purpose of this research is to reveal the relationship between the value of cynicism in the Qur'an in revitalizing morals due to the impact of globalization. This study uses qualitative research with the type of literature review research (library search) using a thematic method (maudhu'i) by collecting verses in the Qur'an related to the concepts of happiness and luck. The results of this study show that the relationship between cynicism and the Qur'an resulting from the terms falaha and fariha is happiness by fulfilling significant primary needs. The value of faith, the value of worship, the value of morals, and the value of social education. As for pursuing morality in the development of globalization, the value that can control human beings is reviewed. If the incoming value is positive, it can produce true happiness. On the other hand, if the incoming value is negative, it cannot produce happiness as the final goal.